Influência do tempo de extração e da razão amostra: solvente no processo de extração do óleo do caroço do pequi visando a produção de biodiesel - Oster, Vanessa Viebrantz (Universidade Federal do Tocantins, 2017)
The environmental problems caused by the excessive use of energy from petroleum are causing countries seek to diversify sources of energy. Within this context, is that the production of biodiesel from vegetable oils, has been increasing in energy scenario. The extraction of the raw material used in producing these biofuels is an extremely important step, so it is necessary to determine the best form of his achievement, featuring the main chemical and physical factors that affect this process. In order to optimize the extraction process of oil pits pequi, this work was based on the realization of experiments that attempted to identify the approximate oil content in the pits pequi and yet which is the best organic solvent, hexane between ethanol and the mixture of these solvents for oil extraction from the seed pequi for biodiesel production. Starting from the data obtained in the tests performed in this study, it can be observed that the pits pequi has a high content of oil, around 31%, much higher than found in soy beans, which today is raw - material basis for biodiesel production. It was also observed that mixtures of two organic solvents (hexane + ethanol) at a ratio of 1:1 was more efficient in the process of Extracting approximately 34% of the oil present in the pits pequi.